2015
DOI: 10.1021/acs.est.5b03078
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Structure–Activity Relationship (QSAR) for the Oxidation of Trace Organic Contaminants by Sulfate Radical

Abstract: The sulfate radical anion (SO4•–) based oxidation of trace organic contaminants (TrOCs) has recently received great attention due to its high reactivity and low selectivity. In this study, a meta-analysis was conducted to better understand the role of functional groups on the reactivity between SO4•– and TrOCs. The results indicate that compounds in which electron transfer and addition channels dominate tend to exhibit a faster second-order rate constants (kSO4•–) than that of H–atom abstraction, corroborating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
119
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(123 citation statements)
references
References 78 publications
4
119
0
Order By: Relevance
“…Furthermore, according to Liu et al [66], a Hirshfeld charge may be successfully employed to determine the reactive sites of the electrophilic reactions. Apart from the oxygen atoms, which are probably not involved in the reactions reported in this study, and a high O/C ratio is often correlated with a slow reaction between the molecules and the oxidants [67], the N atom of AB129 may be characterized by the smallest Hirshfeld charge (−0.424), which is even smaller than the second nitrogen (N1: −0.398) from the primary amine located on the anthraquinone. This may provide further confirmation that the first and crucial reaction of the sulfate radical with AB129 is an electron transfer from the -NH-moiety, which splits the AB129 molecule and creates the anthraquinone derivative.…”
Section: Formation Of By-productsmentioning
confidence: 75%
“…Furthermore, according to Liu et al [66], a Hirshfeld charge may be successfully employed to determine the reactive sites of the electrophilic reactions. Apart from the oxygen atoms, which are probably not involved in the reactions reported in this study, and a high O/C ratio is often correlated with a slow reaction between the molecules and the oxidants [67], the N atom of AB129 may be characterized by the smallest Hirshfeld charge (−0.424), which is even smaller than the second nitrogen (N1: −0.398) from the primary amine located on the anthraquinone. This may provide further confirmation that the first and crucial reaction of the sulfate radical with AB129 is an electron transfer from the -NH-moiety, which splits the AB129 molecule and creates the anthraquinone derivative.…”
Section: Formation Of By-productsmentioning
confidence: 75%
“…55 However, studies also showed that simpler ANN models based on smaller training data sets can still provide meaningful results. 14,21,26,30 Given the limited availability of LCI data sets for training, we aimed at developing a simpler ANN model. Data Collection and Preprocessing.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Moreover, the adsorption by CNTs involve quantum size effects; therefore, quantum‐mechanical descriptors for its prediction should be explored . One of our previous study had examined the risk assessment of MWCNTs through the quantum‐mechanical models for the adsorption of biomolecules by MWCNTs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the adsorption by CNTs involve quantum size effects; therefore, quantum-mechanical descriptors for its prediction should be explored. [29,[31][32][33][34] One of our previous study [6] had examined the risk assessment of MWCNTs through the quantum-mechanical models for the adsorption of biomolecules by MWCNTs. The quantum-mechanically computed mean polarizability and the descriptors accounting for instantaneous interactions between the electrons (the electron correlation) were found to be quite reliable in the quantitative prediction of the adsorption coefficients.…”
mentioning
confidence: 99%